Miriam MacMillan Correspondence - MacMillan, Miriam Look, 1905-1987; Macmillan, Mrs. Donald B., 1905-1987; Jacob, Hilda McLeod; Maine State Library (Digital Maine, 2015)
Entries include a typed biographical letter on personal stationery.